An investigation into metaphors related to the concept of "Dignity" in Oliver Twist by Charles Dickens via its Vietnamese version translated by Phan Ngoc - Trương Thị Hồng Minh (The University of Da Nang, 2013)
Introduction; Literature review and theoretical background; Methodology and procedures; ...